1969
DOI: 10.2466/pr0.1969.25.2.503
|View full text |Cite
|
Sign up to set email alerts
|

Hostility Reduction and Performance

Abstract: The study was concerned with the adequacy of several methods for reducing or preventing hostility toward a frustrating teacher and examined whether classroom performance was affected. Two cathartic methods, Rating Scale and Mutual Expression, and two non-cathartic methods, Explanation and Control, were induced. Residual hostility toward the teacher was measured by means of a Teacher Evaluation Form. Results showed that the Explanation method was most effective and the two cathartic methods were least effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…writing a note, engaging in discussion or angry yelling), which is most analogous to Freud's notion of venting and to the advice given to resolve conflict, increases anger relative to not venting (see Feshbach, 1984;Tavris, 1984Tavris, , 1989, for reviews). Post-venting anger, as measured in a number of ways (such as hostile statements describing the instigator, evaluations of the instigator or like-dislike ratings, thwarting an instigator's goals, subjects' performance on tasks and physiological measures), have all been shown to be negatively affected by verbal venting of anger (Bohart, 1980;DeCharms and Wilkins, 1963;Ebbesen et al, 1975;Goldman et al, 1969;Harburg et al, 1978;Kahn, 1966;Mallick and McCandless, 1966). Furthermore, recent research has shown negative effects of anger and anger expression in negotiation contexts specifically.…”
Section: A Definition Of Ventingmentioning
confidence: 95%
“…writing a note, engaging in discussion or angry yelling), which is most analogous to Freud's notion of venting and to the advice given to resolve conflict, increases anger relative to not venting (see Feshbach, 1984;Tavris, 1984Tavris, , 1989, for reviews). Post-venting anger, as measured in a number of ways (such as hostile statements describing the instigator, evaluations of the instigator or like-dislike ratings, thwarting an instigator's goals, subjects' performance on tasks and physiological measures), have all been shown to be negatively affected by verbal venting of anger (Bohart, 1980;DeCharms and Wilkins, 1963;Ebbesen et al, 1975;Goldman et al, 1969;Harburg et al, 1978;Kahn, 1966;Mallick and McCandless, 1966). Furthermore, recent research has shown negative effects of anger and anger expression in negotiation contexts specifically.…”
Section: A Definition Of Ventingmentioning
confidence: 95%
“…Student grades depend not only on their ability to score well on some evaluation, but also on the ability of the other students. procedure is to reduce the individual student's control over his grade, thus increasing the intensity of feelings of anxiety (Neale & Katahn, 1968) and frustration (Goldman, Keck, & O'Leary, 1969). Neither of these conditions, when intense, contribute to a humanistic environment.…”
Section: Gradesmentioning
confidence: 99%